Banking Habit Determinants of Back Ward Residents of Urban Area - Gaire, Amrit Kumar Sharma (Journal of Nepalese Management and Research, 2022)
Within this context, the objective of this paper is to understand the factors that influence the banking habit of the backward residents of urban area, in the light of tapping the financially excluded population in the main stream of banking transaction. The survey instrument was used to collect the information from 150 residents of the urban people from the back ward area, who have at least one bank account or are involved in any banking transactions in any financial institution. Regression analysis’s findings indicate that the convenience of banking services, financial transaction security, and motivating factors are the three main elements that influence the banking habit.